2014
DOI: 10.1002/path.4328
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal inclusions of α‐synuclein contribute to the pathogenesis of Krabbe disease

Abstract: Demyelination is a major contributor to the general decay of neural functions in children with Krabbe disease. However, recent reports have indicated a significant involvement of neurons and axons in the neuropathology of the disease. In this study, we have investigated the nature of cellular inclusions in the Krabbe brain. Brain samples from the Twitcher mouse model for Krabbe disease and from patients affected with the infantile and late onset forms of the disease were examined for the presence of neuronal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
122
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(135 citation statements)
references
References 92 publications
13
122
0
Order By: Relevance
“…Additionally, neuronal source would be consistent with the colocalization of TnC foci that also stained for Thioflavin-S in the twitcher mouse brain. These findings are also in agreement with our recent report on the development of intraneuronal inclusions containing α-synuclein in GLD (51). Further analysis of GLD pathology is needed to improve our understanding of the cellular source of TnC in GLD and to characterize the composition of extracellular plaques identified by TnC staining patterns in this disease.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Additionally, neuronal source would be consistent with the colocalization of TnC foci that also stained for Thioflavin-S in the twitcher mouse brain. These findings are also in agreement with our recent report on the development of intraneuronal inclusions containing α-synuclein in GLD (51). Further analysis of GLD pathology is needed to improve our understanding of the cellular source of TnC in GLD and to characterize the composition of extracellular plaques identified by TnC staining patterns in this disease.…”
Section: Discussionsupporting
confidence: 94%
“…At MS lesions, increased TnC may have a beneficial role to promote cell growth but it is also possible that prolonged TnC elevations may also prevent the migration of progenitor cells necessary for mediating repair (49, 50). TnC deposits in twitcher brain exhibited a unique pattern of plaque-like clustering in multiple brain regions and some TnC-positive clusters were positive for Thioflavin-S, an amyloid marker (51). Additionally, neuronal source would be consistent with the colocalization of TnC foci that also stained for Thioflavin-S in the twitcher mouse brain.…”
Section: Discussionmentioning
confidence: 99%
“…The aggregation of αS is closely related to several neurodegenerative diseases including Parkinson’s disease (PD) [1, 3]. Recently it was found that αS was present in aggregates of the Krabbe disease and apparently prone to fibrillization in the presence of psychosine [4]. αS adopts different conformations under various environments.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, psychosine has also been found to alter the angiogenesis process in the murine model, and linked to neuronal inclusion of misfolded and aggregated α-synuclein in postmortem brains from both infantile and late onset KD patients [10, 11]. These studies all point to potential autonomous neuronal dysfunction independent of myelin defects in leukodystrophic pathology, which may in fact precede myelin loss.…”
Section: Introductionmentioning
confidence: 99%